Fungsi Otoritas Jasa Keuangan terhadap Perlindungan Konsumen di Sektor Perbankan: Studi Kasus Otoritas Jasa Keuangan Daerah Istimewa Yogyakarta - Kristina Murniati Beda (Lembaga Pengembangan Kinerja Dosen, 2025)
The Financial Services Authority (Otoritas Jasa Keuangan/OJK) plays a strategic role in ensuring the protection of consumer rights in the banking sector. Along with the increasing complexity of financial services, the potential for consumer rights violations has also risen, including misuse of personal data, administrative errors, and unfair dispute resolution. This study aims to analyze how OJK’s supervisory functions in safeguarding consumer rights in the banking sector can be effectively implemented. A socio-juridical method was used, employing legislative approaches, conceptual analysis, and case studies. Theories applied include legal liability theory, consumer protection theory, and banking supervision theory. Data were obtained from legal documents, OJK annual reports, and interviews with relevant parties. The findings indicate that although OJK has adequate supervisory instruments, such as administrative sanctions and consumer complaint systems, implementation still faces challenges, including limited human resources, lack of consumer education, and resistance from some banking institutions to strict supervision. This study implies that strengthening OJK’s institutional capacity and enhancing collaboration with banking institutions are necessary to ensure effective consumer rights protection.